Reliability of wearable microsensors to measure physical activity in handball - Spencer, M.; Holme, B. R.; Luteberget, L. S. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction In recent years, there has been an increased use of wearable tracking technology to measure the physical activity in elite team sports. However, there is currently limited published information on the reliability of these devices (Chambers et al., 2015). Therefore, the aim of this study was to assess the reliability and sensitivity of a commercially available microsensor technology to measure the specific physical activity demands in handball. Methods A total of twenty-two, male and female, elite and highly-trained handball players (age, 22.6 ± 3.7 years; body mass, 84.0 ± 14.2 kg; height, 184.4 ± 12.0 cm; mean ± SD) participated in the study. The subjects were instrumented with two devices (Optimeye S5, Catapult Sports, Melbourne, Australia), and partook either in a laboratory assessment (n = 10) or field assessment (n = 12). The laboratory assessment consisted of seven different handball specific movement tasks. The field assessment consisted of twelve handball-training sessions. Selected inertial movement analysis (IMA) variables were extracted from the manufacture`s software (Catapult Sprint, Catapult Sports, Melbourne, Australia), including IMA magnitude and counts, in addition to Player-Load™. The reliability and sensitivity was estimated using typical error ± 90% CI (expressed as coefficient of variation [CV]) and smallest worthwhile different (SWD) (Hopkins, 2015). Results Laboratory assessment: IMA magnitude showed good reliability (CV 2.9%) in wellcontrolled movement tasks. The CV increased (4.4 to 8.2%) in more chaotic movement tasks. Field assessment: IMA counts showed a good reliability (CV 2.4%) when displayed as total counts. However, the CV increased when categorized into low (1.5-2.5 m.s-1; 2.9%), medium (2.5-3.5 m.s-1; 5.5%) and high (>3.5 m.s-1; 5.6%) intensity bands. Medium/high band (combined) showed a CV of 3.9%. The CV for low, medium/high and total counts was less than the SWD. Furthermore, it was observed a good reliability (CV 0.9%) for PlayerLoad™, which was less than the SWD. Discussion The reliability of IMA counts was acceptable, given that data were expressed as low, medium/ high and total counts. PlayerLoad™ also demonstrated acceptable reliability. As the CV of the aforementioned variables were below the SWD, this suggests that the Optimeye S5 microsensors and its software are sensitive to detect "real and worthwhile" differences in typical handball activity.